Dementia and Physical Activity (DAPA) - an exercise intervention to improve cognition in people with mild to moderate dementia: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Atherton, Nicky; Bridle, Chris; Brown, Deborah; Collins, Helen; Dosanjh, Sukhdeep; Griffiths, Frances; Hennings, Susie; Khan, Kamran; Lall, Ranjit; Lyle, Samantha; McShane, Rupert; Mistry, Dipesh; et al.
Abstract Background Dementia is more common in older than in younger people, and as a result of the ageing of the population in developed countries, it is becoming more prevalent. Drug treatments for dementia are limited, and the main support offered to people with dementia and their families is generally services to mitigate against loss of function. Physical exercise is a candidate non-pharmacological treatment for dementia. Methods/Design DAPA is a randomised controlled trial funded by the National Institute for Health Research Health Technology Assessment programme to estimate the effect of a 4-month, moderate- to hard-intensity exercise training programme and subsequent advice to remain active, on cognition (primary outcome) at 12 months in people with mild to moderate dementia. Community-dwelling participants (with their carers where possible), who are able to walk 3 metres without human assistance, able to undertake an exercise programme and do not have any unstable or terminal illness are recruited. Participants are then randomised by an independent statistician using a computerised random number generator to usual care or exercise at a 2:1 ratio in favour of exercise. The exercise intervention comprises 29, 1-hour-long exercise classes, run twice weekly at suitable venues such as leisure centres, which include aerobic exercise (on static bikes) and resistance exercise (using weights). Goals for independent exercise are set while the classes are still running, and supported thereafter with phone calls. The primary outcome is measured using ADAS-cog. Secondary outcome measures include behavioural symptoms, functional ability, quality of life and carer burden. Primary and secondary outcomes will be measured at baseline and at 6 and 12 months after randomisation, by researchers masked to participant randomisation in the participants' own homes. An economic evaluation will be carried out in parallel to the RCT, as will a qualitative study capturing the experiences of participants, carers and staff delivering the intervention. Discussion The DAPA study will be the first large, randomised trial of the cognitive effects of exercise on people with dementia. The intervention is designed to be capable of being delivered within the constraints of NHS service provision, and the economic evaluation will allow assessment of its cost-effectiveness. Trial registration DAPA was registered with the ISRCTN database on 29 July 2011, registration numberISRCTN32612072 .